Increasing Young Entrepreneurs Through the WMP DISPORA Program: Peningkatan Wirausaha Muda Melalui Program WMP DISPORA - Chotijah Fanaqi; haryadi mujianto; Falahudin Falahudin; Gita Anggraeni Permana; Neneng Lisna Rahayu Sidiq (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of this service activity is to encourage economic growth in the Garut Regency community through young entrepreneurs in the fields of finance, education and training. The method used is the mentoring method. The Youth and Sports Service (Dispora) carries out entrepreneurial assistance activities by opening the Young Youth Entrepreneurship (WMP) program. Beginner Young Entrepreneurs (WMP) is a form of appreciation from the government to young people who are active in the business world, and have shown results and have the potential to develop. This WMP program provides opportunities for young entrepreneurs who have been running a business for at least three months who pass the business plan criteria and selection to receive assistance in the form of capital, education and soft skills training. Capital assistance can be in the form of money or goods, while to increase entrepreneurial knowledge capacity, one way is by holding soft skills training and WMP comparative studies. The result of this service activity is strengthening education and capital skills for young business actors in Garut Regency which encourages community economic growth through the WMP program. This WMP program contributes to the creation of new jobs, increases economic growth and is one component in supporting a healthy business environment and encouraging the vision of the Garut Regency government 2019-2024.